A Novel UWB TEM Horn Antenna with a Microstrip-Type Feed. (7th September 2015) - Wang, Youcheng; Fang, Guangyou; Su, Hai; Ji, Yicai; Ye, Shengbo; Zhang, Xiaojuan
Abstract : A novel ultra-wideband (UWB) TEM horn antenna fed by a microstrip-type transition is designed. The feeding structure is directly realized by a microstrip line with the merit of compact size and UWB. To broaden the low frequency band, an arc surface is added at the end of the flare plates. Numerical simulation is applied to discuss the effect of the geometry construction which contains the microstrip-type transition and the circular arc surface at the end of radiating arm. Return loss, radiation pattern, and gain of the fabricated antennas are measured. The measured results show that the antenna yields a wide bandwidth ranging from 1 GHZ to 10.3 GHz with return loss less than −10 dB. The antenna also achieves unidirectional radiation patterns with stable antenna gain. These characteristics imply that the compact antenna may be used for detecting buried objects in the wall or UWB communication systems of band like GSM, Wi-Fi, and so forth.